Political economics of external sovereign defaults - Carolina Achury; Christos Koulovatianos; John Tsoukalas (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
We develop a dynamic recursive model where political and economic decisions interact, to study how excessive debt-GDP ratios affect political sustainability of prudent fiscal policies. Rent seeking groups make political decisions - to cooperate (or not) - on the allocation of fiscal budgets (including rents) and issuance of sovereign debt. A classic commons problem triggers collective fiscal impatience and excessive debt issuing, leading to a vicious circle of high borrowing costs and sovereign default. We analytically characterize debt-GDP thresholds that foster cooperation among rent seeking groups and avoid default. Our analysis and application helps in understanding the politico-economic sustainability of sovereign rescues, emphasizing the need for fiscal targets and possible debt haircuts. We provide a calibrated example that quantifies the threshold debt-GDP ratio at 137%, remarkably close to the target set for private sector involvement in the case of Greece.
urn:nbn:de:hebis:30:3-382782
Keywords: H63; F34; F36; G01; E44; E43; D72; 330; sovereign debt; rent seeking; world interest rates; international lending; incentive compatibility; tragedy of the commons; EU crisis; Grexit; Graccident